The problem of assessing the effects of low-dose exposure - Нурсултанова, Н; Жумадилов, К (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The essence of the method of EPR spectrometry is that in the enamel of the teeth under the action of radiation produces stable long-lived radicals, which are dependent on the radiation and its dose. This allows the use of enamel as a natural dosimeter. Information on the accumulated dose in such a dosimeter is read by the EPR spectra of the teeth. The main components of EPR spectrometry are native and radiation-induced signals. For the study take teeth that were removed according to dental indications, the treatment of which was carried out with the latest generation of drilling machines. The impact of boron machines, when processing teeth with high revolutions of rotation, causes the formation of paramagnetic centers in the enamel of the teeth. Since the mechanically-induced signal is in the same spectral region with the radiation-induced signal, their superposition leads to an increase in the amplitude of the dosimetric signal and, as a consequence, to overestimate the dose reconstructed from the EPR spectra of the tooth enamel.